Considere a equação x² – 3x – 17 = 0 e sejam r e s suasraízes. Calcule r² + s².
Soluções para a tarefa
Respondido por
0
x²-3x-17=0
![\frac{-(-3)+- \sqrt{(-3)^2-4*1*(-17)} }{2*1}= \frac{3+- \sqrt{77} }{2} \frac{-(-3)+- \sqrt{(-3)^2-4*1*(-17)} }{2*1}= \frac{3+- \sqrt{77} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B-%28-3%29%2B-+%5Csqrt%7B%28-3%29%5E2-4%2A1%2A%28-17%29%7D+%7D%7B2%2A1%7D%3D+%5Cfrac%7B3%2B-+%5Csqrt%7B77%7D+%7D%7B2%7D++)
![x1= \frac{3+ \sqrt{77} }{2} x1= \frac{3+ \sqrt{77} }{2}](https://tex.z-dn.net/?f=x1%3D+%5Cfrac%7B3%2B+%5Csqrt%7B77%7D+%7D%7B2%7D+)
![x2=\frac{3- \sqrt{77} }{2} x2=\frac{3- \sqrt{77} }{2}](https://tex.z-dn.net/?f=+x2%3D%5Cfrac%7B3-+%5Csqrt%7B77%7D+%7D%7B2%7D+)
![( \frac{3+ \sqrt{77} }{2})^2+ (\frac{3- \sqrt{77} }{2})^2= 43 ( \frac{3+ \sqrt{77} }{2})^2+ (\frac{3- \sqrt{77} }{2})^2= 43](https://tex.z-dn.net/?f=%28+%5Cfrac%7B3%2B+%5Csqrt%7B77%7D+%7D%7B2%7D%29%5E2%2B+%28%5Cfrac%7B3-+%5Csqrt%7B77%7D+%7D%7B2%7D%29%5E2%3D+++43)
Perguntas interessantes